The lived experience of parents whose children discharged to home after cardiac surgery for congenital heart disease - Simeone, Silvio; Platone, Nicol; Perrone, Marco; Marras, Valentina; Pucciarelli, Gianluca; Benedetti, Martina; Dell'Angelo, Grazia; Rea, Teresa; Guillari, Assunta; Da Valle, Paola; Gargiulo, Gianpaolo; Botti, Stefano; et al. (Acta Biomedica Atenei Parmensis, 2018)
Background: Congenital Heart Diseases (CHDs) afflicting children are estimated in 8 per 1000 live births. Recent advances in surgery and medical treatments allowed an improvement in survival rates leading to changes in diseases management as chronic conditions. Parents involvement during clinical pathways is considered an essential component of care, but frequently they experience stress and anxiety conditions during the care path. These feelings are typical of the pre and peri-operative period, however they don’t disappear easily and sometimes they can increase after hospital discharge, affecting the family environment and its behaviors. Aim of the work: The purpose of this qualitative study is to examine the lived experience of parents during the time just after their children return home from hospital after undergoing surgery for CHD. Methods: Parents were enrolled and interviewed as a prepositive sampling until concept saturation using Cohen’s phenomenology approach. A quantitative approach was also applied using SF-12 questionnaire. The study was conducted in two Italian hospitals: the Pediatric Heart Surgery Center of the Fondazione Toscana G. Monasterio Institute in Massa and the Pediatric Cardiac Surgery Center of the Federico II University Hospital in Naples. Results: The main themes emerged after the analysis were “happiness and uncertainty”; “chronic psychophysical fatigue”; “the rediscovery of a strong link with health care professionals”. Conclusions: Fully understand the life experience of these families will allow the implementation of targeted health interventions through the implementation of shared strategies and tools to reduce families and children discomfort after hospital discharge.